The effect of implants on gain of steers and heifers grazing native grass - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 1996)
Four trials were con ducted to determine the effect of different implants on steers and heifers grazing native grass pastures for different lengths of time. In addition, two groups of steers were followed through a feeding period to determine if previous implanting had a residual effect on gain. The implanted (Ralgrofi, Ralgrofi Magnum , Synovex Sfi) steers gained faster than the controls; however, no differences in gain occurred among implants. In the finishing group that went on grass at 687 lb, implants had no effect on subsequent feedlot gain. In the second group (on grass at 569 lb and grazing for 80 days), controls gained faster in the feedlot than those that ha d been implanted on grass, resulting in essentially equal weights for all treatments. Among the heifer groups, no differences occurred in pasture gains. Genetic differences in cattle, length o f grazing, and other factors may change implant results.
Keywords: Cattlemen' s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Implants; Native grass; Stocker cattle gains